The Impact of Nutritional Intake on Immune Function and Resilience Against Infectious Diseases in Adults - Ruslan, Hardiyanti; Riskullah, Mega; Karim, Andini (ScieClouds Publishing, 2024)
This study explores the role of nutrition in immune function and resilience against infectious diseases in adults aged 18 to 65 years. Using a quantitative, cross-sectional design, the research examines the relationship between dietary intake and immune markers, as well as the incidence of infectious diseases over a six-month period. A total of 300 participants from a specific urban area were assessed for nutrient intake using a food frequency questionnaire (FFQ) and a 24-hour dietary recall, while immune function was measured through blood biomarkers, including white blood cell count, interleukin-6, and immunoglobulin G levels. The results indicated significant positive correlations between nutrient intake (especially vitamins C and D, and omega-3 fatty acids) and immune function markers, with higher nutrient intake linked to improved immune responses. The study also revealed that participants following the Mediterranean diet had the highest immune function and lowest frequency of infections, while those on low-quality diets experienced poorer immune health and more frequent infections. These findings underscore the critical role of nutrition in modulating immune function and enhancing resilience against infections. This study contributes to the growing body of evidence supporting the beneficial effects of a balanced, nutrient-rich diet on immune health and highlights the importance of dietary interventions for improving public health outcomes.